Communication essentials : the tools you need to master every type of professional interaction - Guinn, Trey (McGraw Hill's Business Essentials, 2022)
No matter how great your knowledge, expertise, or experience, poor communication skills undermine your ability to get your message across, achieve your objectives, and build crucial relationships. To advance your career-and succeed in other aspects of life, as well-building theses skills is essential. In Communication Essentials, expert Trey Guinn takes you step-by-step through the process of improvement, from understanding the importance of message clarity to specific, goal-based strategies to develop and maximize your skills. In Part I: The Essentials, he covers the fundamentals, from why and how we communicate and what effective communication looks like to how it can all go wrong. In Part II: The Essentials Applied, he provides practical advice on identifying goals, owning your message, and anticipating how your audience will perceive you, the messenger. Finally, in Part III: Beyond the Essentials, you'll find practical tips to help you communicate your way into a job, improve your digital communication, work through difficult conversations, and much more. Packed with insights, anecdotes, exercises, and Essential Takeaways to wrap up each chapter, Communication Essentials ensures you'll walk away feeling fully equipped and prepared to put your skills into action right away.